Extraosseous Intradural Chondrosarcoma of the Cervical Spine: A Case Report with Brief Review of Literature - Elizabeth Presutto; Sejal Patel; Joseph Fullmer; Sajeev Ezhapilli (Case Reports in Radiology)
Mesenchymal chondrosarcoma (MCS) is a malignant cancer of the cartilage that accounts for less than 1% of all chondrosarcomas and typically occurs within the bone. One-third of all mesenchymal chondrosarcomas are extraosseous soft tissue sarcomas, rendering this as an uncommon entity. We report a rare case of an extraosseous chondrosarcoma with the cervical spinal canal in a 21-year-old male. The purpose of this case report is to discuss the imaging characteristics of this pathology proven diagnosis.